The Effect of Using Virtual Reality Method on the Learning Practice of Suturing Procedure in Students of Surgical Technology - Malek Mohammadi, Nahid; Najimi, Arash; Ghadami, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Virtual system training is one of the new methods of skill training. Virtual reality technology has been used for several decades in various job training programs, including surgery. This study aimed to evaluate the effect of using the virtual reality method on the level of learning suturing practice in operating room students of Isfahan University of Medical Sciences in 2019. In this quasi-experimental study, 64 operating room students of Isfahan Nursing and Midwifery Faculty were randomly assigned into two groups of traditional training (n=32) and virtual reality training (n=32) after obtaining their written consent. Data were collected through a researcher-made checklist (suturing practice), used after confirming its content validity and reliability. Data were analyzed through SPSS 16 software using descriptive and analytical tests with a significance level of p<0.05. The mean scores of learning suturing practice were 10.44±2.03 in the traditional group and 9.87±3.20 in the virtual reality training group. There was no significant difference between the traditional training group and the virtual reality training group after providing the training (p=0.05). Although the mean scores of learning the suturing practice were the same in both training methods, it seems that applying virtual reality training along with traditional training can have a significant role in improving students’ suturing practice learning and reducing educational costs.